TRANSFER KEBIJAKAN INTERNASIONAL DALAM TATA KELOLA IKLIM: IMPLEMENTASI NILAI EKONOMI KARBON INDONESIA MELALUI KYOTO PROTOCOL DAN PARIS AGREEMENT - Yovana, Kesi; Andatara, Kaila (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This research aims to analyze the implementation of the Kyoto Protocol and the Paris Agreement as global climate agreements in relation to Indonesia’s carbon trading policy, particularly through Presidential Regulation Number 98 of 2021 and its derivative ministerial regulations. The study adopts a qualitative explanatory approach, offering insight into the international climate regime under the UNFCCC, as embodied in the Kyoto Protocol and the Paris Agreement. Theoretical frameworks used include liberalism, international environmental regimes, green economy, and carbon trading. The findings indicate that Indonesia translates the outcomes of international climate negotiations into national policy through the issuance of Presidential Regulation Number 98 of 2021 and its supporting regulatory framework.